A physiological and biomechanical comparison of over-ground, treadmill and ergometer wheelchair propulsion - Mason, B.; Lenton, J.; Leicht, C.; Goosey-Tolfrey, V. L. (Journal of Sports Sciences, 2014)
The purpose of the study was to determine which laboratory-based modality provides the most valid physiological and biomechanical representation of over-ground sports wheelchair propulsion. Fifteen able-bodied participants with previous experience of wheelchair propulsion performed a 3-minute exercise trial at three speeds (4, 6 and 8 km/h) in three testing modalities over separate sessions: (i) over-ground propulsion on a wooden sprung surface; (ii) wheelchair ergometer propulsion; (iii) treadmill propulsion at four different gradients (0%, 0.7%, 1.0% and 1,3%). A 0.7% treadmill gradient was shown to best reflect the oxygen uptake (7.3 to 9.1% coefficient of variation (CV)) and heart rate responses (4.9 to 6.4% CV) of over-ground propulsion at 4 and 6 km/h. A 1.0% treadmill gradient provided a more valid representation of oxygen uptake during over-ground propulsion at 8 km/h (8.6% CV). Physiological demand was significantly underestimated in the 0% gradient and overestimated in the 1.3% gradient and wheelchair ergometer trials compared to over-ground trials (P<0.05). No laboratory-based modality provided a valid representation of the forces applied during OG (= 18.4% CV). To conclude, a 0.7% treadmill gradient is recommended to replicate over-ground wheelchair propulsion at lower speeds (4 and 6 km/h) whereas a 1.0% gradient may be more suitable at 8 km/h.